ANALISIS KESALAHAN SISWA SMP PADA MATERI STATISTIKA DITINJAU DARI GAYA BELAJAR DENGAN MENGGUNAKAN INSTRUMEN CRI - Saidah, Aina (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
Students often experience errors during the learning process, like errors in reading and digesting questions. Characteristics of students in understanding a material affect errors in solving problems, one of which is the learning style. Learning style is a way that is used by students to absorb and process information from the environment. There are three types of learning styles, including visual, auditory, and kinesthetic. This research is a qualitative descriptive which aims to categorize students' errors in statistical material in terms of learning styles using the CRI instrument. The subjects in this study were 31 students who had studied statistics. The results of this study indicate that students who have a visual learning style have transformation errors and errors in understanding questions. Students with auditory learning style have transformation errors and errors in understanding basic concepts. Students with kinesthetic learning style have errors in remembering basic concepts and transformation errors.